Developing independent investigators for clinical research relevant for Africa - Manabe Yukari C; Katabira Elly; Brough Richard L; Coutinho Alex G; Sewankambo Nelson; Merry Concepta (BMC, 2011)
Abstract Sustainable research capacity building requires training individuals at multiple levels within a supportive institutional infrastructure to develop a critical mass of independent researchers. At many African medical institutions, a PhD is important for academic promotion and is, therefore, an important focal area for capacity building programs. We examine the training at the Infectious Diseases Institute (IDI) as a model for in-country training based on systems capacity building and attention to the academic environment. PhD training in Africa should provide a strong research foundation for individuals to perform independent, original research and to mentor others. Training the next generation of researchers within excellent indigenous academic centers of excellence with strong institutional infrastructure will empower trainees to ask regionally relevant research questions that will benefit Africans.